SSH: Shark Search Algorithm and Gray-Box Program with Hadoop in Distributed Network - Indhunisha, R; Srinath, MV (International Journal of Computer Sciences and Engineering, 2025)
Huge data is the term on the other hand an accumulation of data sets which are expansive also, complex, it contain organized also, unorganized both sort of data. Data comes from everywhere, sensors utilized to gather climate information, posts to social media sites, digital pictures also, and videos and so forth this data is known as enormous data. Useful data can be extracted from this enormous data with the help of data mining. Data mining is a system on the other hand discovering interesting designs as well as descriptive, understand capable models from expansive scale data. In this paper we overviewed sorts of enormous data also, challenges in enormous data on the other hand future.